RESTFul Web Service Untuk Sistem Pencatatan Transaksi Studi Kasus PT. XYZ - Penidas Fiodinggo Tanaem; Danny Manongga; Ade Iriani (Maranatha University Press, 2016)
Utilization of current technology is a major influence in both of individuals and organizations, as well as PT. XYZ. Thus the technology is always developed with the aim to meet every requirement for its users. The objectives to be achieved from this research is discusses the RESTful Web Service architecture that uses security by implementing JSON Web Token and use was in the system of recording transactions in PT XYZ. This research resulted in a RESTful Web Service architecture applied in PT. XYZ